What do we know about the role of enterprise architecture in enterprise integration? A systematic mapping study. Issue 1 (8th February 2016) - Banaeianjahromi, Negin; Smolander, Kari
Abstract : Purpose: – Constant changes in the environment seem to have become the biggest challenge of a modern enterprise, which emphasizes the constant need to integrate the enterprise into its changing environment. Aiming at eliminating the integration challenges, EA is proposed as a solution. The purpose of this paper is to survey and analyse the available literature on determining the role of EA in EI and also to identify gaps and state-of-the-art in research. Design/methodology/approach: – This paper presents a systematic mapping study that found 50 papers in the intersection of EA and EI, these papers were surveyed, analysed, and classified with respect to research focus, research method, and paper type. Findings: – Based on the analyses of the final 50 articles, the authors realized that "EA framework" is the dominating research focus of these studies. "Evaluation research" is recognized as the most common paper type in this area. However, "Experience paper" was a rare paper type in this research domain. "Constructive research" and "Case study/multiple case studies" are widely applied as the research method. "Survey", "Delphi study" and "Grounded theory" are the least employed research methods. The conclusion was that there is a need for empirical research in this area. After analysing the articles based on their publication year, the authors also noticed a significant growth between 2004 and 2010. After 2010 the number of publications had a downward trend. Originality/value: – To the knowledge of the authors, this study is the first systematic literature study regarding the role of EA in EI. There are several systematic literature reviews about the EA or EI separately but none of them has addressed the specific realm of the research. Hence, the goal of this study is to provide a map of existing literature to enable improvement of the practice with the known research results and to identify gaps for future research.